Serum Exosomal MicroRNA-21, MicroRNA-126, and PTEN Are Novel Biomarkers for Diagnosis of Acute Coronary Syndrome - Ling, Hao; Guo, Ziyuan; Shi, Yongfeng; Zhang, Lei; Song, Chunli (Frontiers in Physiology, 2020)
Acute coronary syndrome (ACS) is a serious threat to public health. Based on clinical manifestations, ACS can be classified into unstable angina (UA) pectoris and acute myocardial infarction (AMI). The purpose of this study was to explore the possibility of using serum exosomal microRNA (miR)-126, miR-21, and phosphatase and tensin homolog (PTEN) expression levels as biomarkers of UA and AMI and to investigate whether these levels were positively correlated with the severity of coronary stenosis based on the Gensini score. Exosomes were isolated by ultracentrifugation from the serum of 34 patients with AMI, 31 patients with UA, and 22 healthy controls. The isolated exosomes were characterized by electron microscopy and particle size analysis; exosomal identity was further confirmed by western blotting using exosome-specific antibodies. Real-time quantitative polymerase chain reaction indicated that the serum exosomal levels of miR-126 and miR-21 were significantly higher in the patients with UA and AMI than in the healthy controls. Enzyme-linked immunosorbent assay showed that the serum exosomal PTEN levels were significantly higher in the UA and AMI groups than in the control group. Receiving operating characteristic curve analysis demonstrated the diagnostic efficiency of serum exosomal miR-126, miR-21, and PTEN levels for predicting AMI and UA. In addition, the circulating exosomal miR-126 level was positively correlated with the severity of coronary artery stenosis in patients with UA and AMI based on the Gensini score.